Geometric phase kickback in a mesoscopic qubit-oscillator system - Vacanti, G; Fazio, R; Kim, MS; Palma, G; Paternostro, M; Vedral, V (2011)
We illustrate a reverse Von Neumann measurement scheme in which a geometric phase induced on a quantum harmonic oscillator is measured using a microscopic qubit as a probe. We show how such a phase, generated by a cyclic evolution in the phase space of the harmonic oscillator, can be kicked back on the qubit, which plays the role of a quantum interferometer. We also extend our study to finite-temperature dissipative Markovian dynamics and discuss potential implementations in micro and nano-mechanical devices coupled to an effective two-level system.